Regulation and functional roles of rebound potentiation at cerebellar stellate cell—Purkinje cell synapses - Hirano, Tomoo; Kawaguchi, Shin-ya (Frontiers in Cellular Neuroscience, 2014)
Purkinje cells receive both excitatory and inhibitory synaptic inputs and send sole output from the cerebellar cortex. Long-term depression, a type of synaptic plasticity, at excitatory parallel fiber–Purkinje cell synapses has been studied extensively as a primary cellular mechanism of motor learning. On the other hand, at inhibitory synapses on a Purkinje cell, postsynaptic depolarization induces long-lasting potentiation of GABAergic synaptic transmission. This synaptic plasticity is called rebound potentiation (RP), and its molecular regulatory mechanisms have been studied. The increase in intracellular Ca2+ concentration caused by depolarization induces RP through enhancement of GABAA receptor (GABAAR) responsiveness. RP induction depends on binding of GABAAR with GABAAR associated protein (GABARAP) which is regulated by Ca2+/calmodulin-dependent kinase II (CaMKII). Whether RP is induced or not is determined by the balance between phosphorylation and de-phosphorylation activities regulated by intracellular Ca2+ and by metabotropic GABA and glutamate receptors. Recent studies have revealed that the subunit composition of CaMKII has significant impact on RP induction. A Purkinje cell expresses both alpha- and beta-CaMKII, and the latter has much higher affinity for Ca2+/calmodulin than the former. It was shown that when the relative amount of alpha- to beta-CaMKII is large, RP induction is suppressed. The functional significance of RP has also been studied using transgenic mice in which a peptide inhibiting association of GABARAP and GABAAR is expressed selectively in Purkinje cells. The transgenic mice show abrogation of RP and subnormal adaptation of vestibulo-ocular reflex, a type of motor learning. Thus, RP is involved in a certain type of motor learning.